Building domestic capabilities in renewable energy: a case study of Egypt - Georgeta Vidican (Deutsches Institut für Entwicklungspolitik (DIE), 2012)
The wide availability of renewable energy sources in the Middle East and North Africa (MENA) is at the core of several large-scale European initiatives to support clean energy generation in the region and import part of it to Europe. Given the current socio-economic and political challenges in the MENA region, this goal could be realized if the renewable energy sector becomes a channel for local industrial development, private sector competitiveness and a source of employment and capacity building. Within the specific context of Egypt, this study assesses: (1) what is the potential for localizing the value chain for solar and wind technologies; (2) what institutional and political obstacles impede the domestic benefits; and (3) what policy recommendations could be proposed for national policy-makers and international cooperation agencies to support this development process. The study finds that while important local technological capabilities exist, specific policy measures need to be considered in several areas: energy subsidy reform, supply chain development, knowledge and R&D capabilities. Moreover, Egyptian policy-makers should disseminate a new narrative to mobilize alliances between various stakeholder groups to make renewable energy viable for Egypt.
Keywords: 330; Entwicklungsfinanzierung und öffentliche Finanzen; Energie; Governance; Technologie und Innovation; Erneuerbare Energie; Angepasste Technologie; Förderung erneuerbarer Energien; Ägypten